Peningkatan Kewaspadaan Hipertensi Melalui Pemeriksaan Tekanan Darah sebagai Deteksi Dini pada Populasi Lanjut Usia di Panti Werda Hana - Wijaya, Christian; Firmansyah, Yohanes; Syarifah, Andini Ghina; Alifia, Tosya Putri; Kurniawan, Junius; Gunaidi, Farell Christian (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Hypertension is a major cause of morbidity and mortality worldwide, and its prevalence increases with age. Hypertension is a chronic condition characterised by increased arterial blood pressure. In Indonesia, the prevalence of hypertension ranges from 45.9% in people aged 55-64 years to 63.8% in people aged 75 years and over. Hypertension is known as the "silent killer" because it often appears without symptoms and requires early detection to prevent complications such as heart disease, stroke and kidney failure. This activity uses the PDCA (Plan-Do-Check-Act) method for continuous improvement in the health examination process, including blood pressure measurement. 61 participants (14 men and 47 women) participated in this activity at the Hana Nursing Home in South Tangerang. A physical examination revealed that 11 people (18.03%) had hypertension. Regular monitoring is essential to identify high-risk individuals early, allowing them to take preventive measures and manage their blood pressure effectively. This approach can significantly reduce the risk of serious complications and improve the quality of life for seniors.